2014
DOI: 10.1007/s12640-014-9474-z
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Manganese Exposure and Hydroxyl Radical Formation in Rat Brain

Abstract: The present study was designed to investigate the role of pre- and postnatal manganese (Mn) exposure on hydroxyl radical (HO•) formation in the brains of dopamine (DA) partially denervated rats (Parkinsonian rats). Wistar rats were given tap water containing 10,000 ppm manganese chloride during the duration of pregnancy and until the time of weaning. Control rat dams consumed tap water without added Mn. Three days after birth, rats of both groups were treated with 6-hydroxydopamine at one of three doses (15, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…5E and G). Oxidative stress has been implicated in Mn neurotoxicity (Milatovic et al, 2009;Herná ndez et al, 2011;Stephenson et al, 2013), and it has been reported that Mn induces production of H 2 O 2 in vitro (Posser et al, 2009) and hydroxyl radical in vivo (Bałasz et al, 2015). This result demonstrates that the hippocampus is susceptible to oxidative stress induced by perinatal Mn exposure and the effects of excessive levels of Mn in this region have consequences for the antioxidant defense system in rats that last into adulthood (PND70).…”
Section: Discussionmentioning
confidence: 85%
“…5E and G). Oxidative stress has been implicated in Mn neurotoxicity (Milatovic et al, 2009;Herná ndez et al, 2011;Stephenson et al, 2013), and it has been reported that Mn induces production of H 2 O 2 in vitro (Posser et al, 2009) and hydroxyl radical in vivo (Bałasz et al, 2015). This result demonstrates that the hippocampus is susceptible to oxidative stress induced by perinatal Mn exposure and the effects of excessive levels of Mn in this region have consequences for the antioxidant defense system in rats that last into adulthood (PND70).…”
Section: Discussionmentioning
confidence: 85%
“…It should be noted that disruption of the processes of barrier genesis during the development of the CNS can have a significant effect not only in the early postnatal period, but also in the long term of individual development. In one of the studies, it was shown that if this process is triggered in early ontogenesis, then it is able to persist throughout the adult life of the organism with a tendency to progress and globalize emerging disorders, even in the absence of an influencing factor (Bałasz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Mn is an essential trace element that supports numerous physiological functions such as protein metabolism, energy metabolism, and the development of bone and cartilage. However, it has been noted that excessive of Mn exposure can lead to neurotoxicity and reproductive toxicity (Bałasz et al, 2015; Claus et al, 2011; Srivastava et al, 2013; Tarale et al, 2016). Williams et al (2012) reported that impaired fertility and sexual function, decreased sperm count, and viability have been found in male workers exposed to Mn dust.…”
Section: Introductionmentioning
confidence: 99%